2022
DOI: 10.1159/000526425
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies against Central Nervous System Antigens and the Serum Levels of IL-32 in Patients with Schizophrenia

Abstract: <b><i>Background:</i></b> Schizophrenia is a disease of the nervous system, and immune system disorders can affect its pathogenesis. Activation of microglia, proinflammatory cytokines, disruption of the blood-brain barrier due to inflammation, activation of autoreactive B cells, and consequently the production of autoantibodies against system antigens are among the immune processes involved in neurological diseases. Interleukin-32 (IL-32) is a proinflammatory cytokine that is essential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Park et al 15 reported that anti-Ma2 antibody encephalitis could cause psychiatric symptoms like aggressiveness, memory impairment, decreased speech, anxiety, disorganized language, and depressed mood. In a recent study, the prevalence of anti-GAD and anti-Ri antibodies in schizophrenia patients was higher than in controlled patients 16 . Keshavarz et al 16 showed that among 40 patients treated for schizophrenia, eight were positive for anti-GAD antibody, five for anti-Ri antibody, two for anti-CV2 antibody, one for anti-Hu antibody, and one for anti-CARP antibody.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Park et al 15 reported that anti-Ma2 antibody encephalitis could cause psychiatric symptoms like aggressiveness, memory impairment, decreased speech, anxiety, disorganized language, and depressed mood. In a recent study, the prevalence of anti-GAD and anti-Ri antibodies in schizophrenia patients was higher than in controlled patients 16 . Keshavarz et al 16 showed that among 40 patients treated for schizophrenia, eight were positive for anti-GAD antibody, five for anti-Ri antibody, two for anti-CV2 antibody, one for anti-Hu antibody, and one for anti-CARP antibody.…”
Section: Discussionmentioning
confidence: 86%
“…In a recent study, the prevalence of anti-GAD and anti-Ri antibodies in schizophrenia patients was higher than in controlled patients 16 . Keshavarz et al 16 showed that among 40 patients treated for schizophrenia, eight were positive for anti-GAD antibody, five for anti-Ri antibody, two for anti-CV2 antibody, one for anti-Hu antibody, and one for anti-CARP antibody. Several literature publications have suggested a relationship between schizophrenia and antineuronal antibodies in the context of PNS 10 , 15 , 16 .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Looking at regional analysis, we have identified several significant DMRs annotated in genes related to inflammatory and immune processes, such as LTA , GFI1 , ARID5B , CD52 , TNFSF13 , SLFN13 , LST1 , TNFRSF1A , CCRL2 , and IL32 . Moreover, some significant genes are known to be related to schizophrenia risk, such as LTA (Arab & Elhawary, 2015 ; Pandey et al, 2018 ), ARID5B (Drago et al, 2014 ), TNFSF13 (Catts & Weickert, 2012 ), TNFRSF1A (Gandal et al, 2018 ), IL32 (Keshavarz et al, 2022 ), LDLRAD4 (Kikuchi et al, 2003 ), and GAS7 (Z. Zhang et al, 2016 ), attention-deficit hyperactivity disorder, like GFI1 (Miyake et al, 2021 ), bipolar disorder, including TNFRSF1A (Gandal et al, 2018 ), and autism spectrum disorder, like TNFRSF1A (Gandal et al, 2018 ) and C11orf21 (Dall’Aglio et al, 2018 ). Notably, another significant gene is LST1 (Leukocyte Specific Transcript 1), which plays a role in immune system regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Schizophrenia is a progressive and chronic psychiatric disorder affecting approximately 0.3 % of people worldwide [ 1 , 2 ]. In recent years, schizophrenia has been considered a heterogeneous condition with differential etiological factors [ 3 ], such as neuroinflammation [ 4 ], genetic abnormalities [ 5 ], and autoimmune disorders [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%